Emotion recognition specialization and context‐dependent risk of anxiety and depression in adolescents. Issue 2 (16th January 2015) - Oldehinkel, Albertine J.; Hartman, Catharina A.; Van Oort, Floor V. A.; Nederhof, Esther
Abstract Background Some adolescents function poorly in apparently benign environments, while others thrive despite hassles and difficulties. The aim of this study was to examine if adolescents with specialized skills in the recognition of either positive or negative emotions have a context‐dependent risk of developing an anxiety or depressive disorder during adolescence, depending on exposure to positive or harsh parenting. Methods Data came from a large prospective Dutch population study (N = 1539). At age 11, perceived parental rejection and emotional warmth were measured by questionnaire, and emotion recognition skills by means of a reaction‐time task. Lifetime diagnoses of anxiety and depressive disorders were assessed at about age 19, using a standardized diagnostic interview. Results Adolescents who were specialized in the recognition of positive emotions had a relatively high probability to develop an anxiety disorder when exposed to parental rejection (Bspecialization*rejection = 0.23, P < 0.01) and a relatively low probability in response to parental emotional warmth (Bspecialization*warmth = −0.24, P = 0.01), while the opposite pattern was found for specialists in negative emotions. The effect of parental emotional warmth on depression onset was likewise modified by emotion recognition specialization (B = −0.13, P = 0.03), but the effect of parental rejection was not (B = 0.02, P = 0.72). In general, the relative advantage of specialists in negative emotions was restricted to fairly uncommon negative conditions. Conclusions Our results suggest that there is no unequivocal relation between parenting behaviors and the probability to develop an anxiety or depressive disorder in adolescence, and that emotion recognition specialization may be a promising way to distinguish between various types of context‐dependent reaction patterns.